Exploring the Supply Chain and Logistics Practises between India and China - Pandiaraju, Vinu Karthick (2011)
India and China continue to rise as economic powers in the globe. The annual bilateral trade value between these two countries is continuously increasing rapidly. The bilateral trade value between India and China in the year 2010 was 60 billion USD and the trade target for the year 2015 is set as 100 billion USD. Despite the enormous amount of trade and business activities happening between both these countries, there have been quite a lot of issues that hinders the trade between them and the companies from India and China face a lot of challenges in interacting with each others. This dissertation report provides a detailed study about the trade between these two countries in the past two decades and explores how far the supply chain and logistics have improved over the years. This report also analyses about the logistics issues faced by companies and the barriers these companies face in entering each other markets. In addition to this various other problems such as the political uncertainties and issues across border are also discussed. A SWOT analysis is being made to interpret various strengths, weaknesses, opportunities and threats that prevail in the bilateral trade between them and thus providing an opportunity to highlight the area of focus for future research. Finally the report concludes with a few suggestions and recommendations that are made with the help of India- China Joint Study Group’s report.